A bioeconomic model applied to a small pelagic species along the Moroccan coast. (10th February 2021) - Agmour, Imane; Bentounsi, Meriem; Achtaich, Naceur; Foutayeni, Youssef El
This paper proposes a case study of five small pelagic species: Sardina pilchrdus, Sardinella, Engraulis encrasicolus, Scomber scombrus and Trachurus exploited by seiners in the maritime zones of Morocco. A comparison is made between the fishing effort calculated using the generalised Nash equilibrium problem and the actual fishing effort given by the National Institute of Fisheries Research. In this work, fishing effort represents the number of fishing trips that must be made by seiners and that allows them to maximise their gain taking into account the preservation of marine species. As a result, we find that master data of the National Institute of Fisheries Research support the outcomes shown in the end of this paper.